PWE-096 The investigation and management of colovesical fistulae in the modern era—a single institutions 12-year experience. (28th May 2012) - Ladwa, N; Sajid, M; McFall, M; Miles, A; Sains, P; Baig, M K
Abstract : Introduction: This aim of this study is to review how investigation and management of colovesical fistulae has progressed in our institution over a 12-year period and to propose a clear protocol to ensure prompt diagnosis and treatment in the future. Methods: A retrospective case note review was conducted of all patients with colovesical fistulae who underwent definitive surgery over a 12-year period. Variables collected include patient demographics, symptoms, investigations, operative data, histology, complications and length of stay. Results: 56 patients (38 male) underwent operative intervention for colovesical fistula. The most common symptoms are pneumaturia (69%), faecaluria (32%) and symptoms associated with recurrent UTIs (68%). Cystoscopy was the most accurate test to identify fistulae (91%) followed by CT (60%) and barium enema (31%). Two patients were unfit for major surgery and underwent palliative loop colostomies. The most common pathology was diverticular disease. Of the 54 remaining patients, 45% underwent laparoscopic resection with a conversion rate of 33% (due to adhesions or multiple abscesses). Sigmoid colectomy, (52%) anterior resection (30%) and hartmanns (9%) are the most common procedures performed. Bladder repair was required in 25% of cases with a further 16% requiring partial resection. All patients received a postoperative cystogram to ensure bladder had healed and 70% of patients were defunctioned to protect the anastomosis. There was no mortality reported peri-operatively; the anastomotic leak rate was 5% and recurrence rate was 5%. Median postoperative stay was 12.5 days (range 4–91) in the laparoscopic group and 16 days (range 6–62) in the open group. Conclusion: Surgical management for colovesical fistulae is effective and safe. Laparoscopic resections are increasing in popularity and deliver encouraging results comparable to open resection. A large multi-centre randomised controlled trial is required to validate its potential benefits over open surgery. Competing interests: None declared.